The design of nonovershooting and nonundershooting multivariable state feedback tracking controllers - Schmid, R.; Ntogramatzidis, Lorenzo (Elsevier BV, North-Holland, 2012)
We consider the use of linear multivariable feedback control to achieve a nonovershooting and nonundershooting step response. Recently, Schmid and Ntogramatzidis (2010) [13] introduced a linear state feedback controller design method to avoid overshoot. In this paper, we describe conditions under which the design method may be modified to avoid undershoot. The method is applicable to square and nonsquare systems, minimum and nonminimum phase systems, and also strictly proper and bi-proper systems.